PENGARUH SISTEM AKUNTANSI, PRINSIP VALUE FOR MONEYDAN TRANSPARANSI TERHADAP KINERJA KEUANGAN DAERAH (STUDI KASUS DI PEMERINTAH DAERAH KOTA MAKASSAR) - Ibrahim H. Ahmad (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The purpose of this study was to determine and analyze the effect of the accounting system, the principle of value for money, and transparency of public policy towards regional financial performance, as well as to determine the factors that most affect the financial performance areas. The population in this study is the employees who work in SKPDs the Government of Makassar. Sampling was done by purposive sampling, a total sample of 72 people, who were selected from 24 work units (SKPD), each taken as many as 3 people. The analytical tool used is quantitative descriptive analysis with multiple linear regression. The results showed that the variable accounting system, the principle of value for money (VFM), and transparency of public policy and a significant positive effect on financial performance in the areas of Makassar on education, either partially or simultaneously with the level of a very close relationship, in which the principle of value for money (VFM) most influence on financial performance in the areas of Makassar on education